Fabrication of Cr2O3: ZnO Nanostructure Thin Film Prepared by PLD Technique as NH3 Gas Sensor - AbdulKareem, S.M.; Suhail, M.H.; Adehmash, I. K. (Iraqi Journal of Science, 2021)
Chromium oxide (Cr2O3) doped ZnO nanoparticles were prepared by pulsed laser deposition (PLD) technique at different concentration ratios (0, 3, 5, 7 and 9 wt %) of ZnO on glass substrate. The effects of ZnO dopant on the average crystallite size of the synthesized nanoparticles was examined By X-ray diffraction. The morphological features were detected using atomic force microscopy (AFM). The optical band gap value was observed to range between 2.78 to 2.50 eV by UV-Vis absorption spectroscopy, with longer wavelength shifted in comparison with that of the bulk Cr2O3 (~3eV). Gas sensitivity, response, and recovery times of the sensor in the presence of NH3 gas were studied and discussed. In the present work, we found that the sensitivity was increased upon increasing the concentration ratio from 3 to 5%wt of ZnO, whereas it was decreased again over that value. Also, we found that the sensitivity was increased when increasing operating temperature, while the response time was decreased. The optimum concentrations ratio for NH3 gas sensitivity at 5%wt ZnO revealed sensitivity of 66.67% and response time of 14s at operating temperature of 300oC and 700mJ PLD energy.